Biogenic carbon matrix with dual-mode adsorption capability: synthesis, characterization and mechanistic insights - Kannan, N; Srinanthakumar, N.; Goonetilleke, A.; McGree, J.; Bandala, E.R. (Elsevier, 2026)
The transformation of biowaste into high-performance functional materials presents a promising strategy for sustainable environmental technologies. In this study, a novel biogenic carbon-based catalytic matrix (CBCM) was synthesized from prawn shell waste, integrating chitin-derived carbon and in-situ formed calcite to yield a hybrid material with distinctive structural and surface characteristics. Comprehensive characterization using X-ray diffraction (XRD) and Fourier-transform infrared spectroscopy (FTIR) revealed a composite architecture featuring both organic (Chitin) and inorganic (Calcite) crystalline domains, along with abundant surface oxygenated functional groups (O–H, C=O, CO–NH, and C–O). These structural attributes underpin the CBCM's dual-mode adsorption capability, enabling simultaneous and efficient uptake of both cationic (Malachite green) and anionic (Congo red) dyes. Kinetic and isotherm analyses highlighted the dominant roles of hydrogen bonding and π-π interactions, directly linked to the material's functional groups and porous surface morphology. Response surface modeling confirmed strong agreement between predicted and experimental adsorption capacities (R 2 = 0.978), underscoring the reliability of the structure-function correlation. This work demonstrates how rational design and valorization of marine biowaste can yield multifunctional materials, with the CBCM serving as a proof-of-concept platform for pollutant capture and broader environmental applications.
Keywords: Catalytic matrix; Kinetic modeling; Predictive modeling; Adsorption